Polyploidisation and Geographic Differentiation Drive Diversification in a European High Mountain Plant Group (Doronicum clusii Aggregate, Asteraceae) - Pachschwöll, Clemens; Escobar García, Pedro; Winkler, Manuela; Schneeweiss, Gerald M.; Schönswetter, Peter (PLOS ONE, 2015)
Range shifts (especially during the Pleistocene), polyploidisation and hybridization are major factors affecting high-mountain biodiversity. A good system to study their role in the European high mountains is the Doronicum clusii aggregate (Asteraceae), whose four taxa (D. clusii s.s., D. stiriacum, D. glaciale subsp. glaciale and D. glaciale subsp. calcareum) are differentiated geographically, ecologically (basiphilous versus silicicolous) and/or via their ploidy levels (diploid versus tetraploid). Here, we use DNA sequences (three plastid and one nuclear spacer) and AFLP fingerprinting data generated for 58 populations to infer phylogenetic relationships, origin of polyploids—whose ploidy level was confirmed by chromosomally calibrated DNA ploidy level estimates—and phylogeographic history. Taxonomic conclusions were informed, among others, by a Gaussian clustering method for species delimitation using dominant multilocus data. Based on molecular data we identified three lineages: (i) silicicolous diploid D. clusii s.s. in the Alps, (ii) silicicolous tetraploid D. stiriacum in the eastern Alps (outside the range of D. clusii s.s.) and the Carpathians and (iii) the basiphilous diploids D. glaciale subsp. glaciale (eastern Alps) and D. glaciale subsp. calcareum (northeastern Alps); each taxon was identified as distinct by the Gaussian clustering, but the separation of D. glaciale subsp. calcareum and D. glaciale subsp. glaciale was not stable, supporting their taxonomic treatment as subspecies. Carpathian and Alpine populations of D. stiriacum were genetically differentiated suggesting phases of vicariance, probably during the Pleistocene. The origin (autopolyploid versus allopolyploid) of D. stiriacum remained unclear. Doronicum glaciale subsp. calcareum was genetically and morphologically weakly separated from D. glaciale subsp. glaciale but exhibited significantly higher genetic diversity and rarity. This suggests that the more widespread D. glaciale subsp. glaciale originated from D. glaciale subsp. calcareum, which is restricted to a prominent Pleistocene refugium previously identified in other alpine plant species.